Discretionary Evidence Loaning as Property Rights Protection for Victims of Motor Vehicle Theft: An Empirical Study on the Modernized Criminal Justice Paradigm - Subekti Subekti; Maldine Ikhtiarsyah Putra; Yoyok Ucuk Suyono; Ernu Widodo; Donny Irawan (Syura: Journal of Law, 2026)
Motor vehicle theft remains a dominant conventional crime that challenges local law enforcement stability. Although recovering stolen vehicles represents a success for investigators, it paradoxically triggers secondary victimization when those vehicles are impounded in police custody for extended periods as court evidence. This study aims to analyze the legal protections provided to victims regarding their property rights and identify the technical-legal obstacles faced by investigators in the field amid the transition toward Indonesia's modernized criminal justice framework. Using empirical legal research with fact and statute approaches, data were gathered through in-depth interviews with investigators at the Tanjungpinang City Police Resort (Polresta Tanjungpinang) and affected victims. The results indicate that legal protection is effectively delivered through transparent Case Progress Reports (SP2HP) and a fast-track, cost-free "evidence loaning" (pinjam pakai barang bukti) mechanism executed within three days based on the victim's economic urgency. However, investigators face significant challenges, including risks of evidence modification or loss before trial and physical tampering with engine and chassis serial numbers by criminals. This study concludes that progressive police discretion successfully bridges the gap between rigid statutory certainty and social utility for crime victims under contemporary legal reforms.